(untitled) (Research, Society and Development, 2023)
Animal Assisted Therapy (AAT) has become a very present intervention in cases of therapy with children with Autistic Spectrum Disorder (ASD), as it helps the patient to develop autonomy and social skills, which are greatly affected for this disorder. The objective of the present study is to know the effects that AAT provides to children with ASD, especially with regard to social skills. Therefore, to define the research question, the PICO strategy was used, defining the central question that guided the study: “In children with autism, is animal-assisted therapy effective for improving social interactions?”. For the collection of information used for the construction of this integrative literature review, 20 scientific articles dated from 2017 to 2022 were analyzed, which were searched in the following databases: Virtual Health Library (BVS), Scientif Electronic Library Online (SciELO) , National Library of Medicine (PubMed), EbscoHost, and Google Scholar. The results found identified that AAT provided positive effects on social skills, autonomy, expression of emotions and reduction of symptoms in children with ASD. In view of this, the AAT proved to be effective as a form of non-drug intervention that beneficially influences the patient’s quality of life and biopsychosocial, since the development of social skills interfere, in a positive way, in school education and, above all, in the child’s interpersonal interactions.